"Non‐Naked" Gold with Glucose Oxidase‐Like Activity: A Nanozyme for Tandem Catalysis. Issue 44 (1st October 2018) - Zhang, Haijiao; Liang, Xin; Han, Lei; Li, Feng
Abstract: It has been widely reported that "naked" gold nanoparticles (Au NPs) without protectors have glucose oxidase (GOx)‐like activity, and the use of protectors can inhibit the GOx‐like activity. Here, "non‐naked" Au NPs with GOx‐like activity are synthesized by using protein as protector. Although "naked" Au NPs have peroxidase‐like activity and GOx‐like activity, the optimal pH ranges of the both activities are obviously different. Fortunately, as‐synthesized "non‐naked" Au NPs show the dual enzyme‐like activities at the same pH. So, "non‐naked" Au NPs can be described as "tandem nanozyme." As another bonus, the participation of protein protector can stabilize the GOx‐like activity and make Au NPs modifiable. Even though Au NPs are connected with graphene oxide (GO), the GOx‐like activity is still not changed. Further, Au NPs‐GO nanocomposites are applied on the one‐pot nonenzymatic glucose colorimetric detection. The "non‐naked" gold not only broadens the species of tandem nanozymes, but also facilitates the functionalization of nanozymes, which is promising for immunoassay, biosensor, and medical treatment. Abstract : "Non‐naked" gold nanoparticles (Au NPs) with the glucose oxidase (GOx)‐like activity are synthesized by using protein as protector. "Non‐naked" Au NPs show tandem enzyme‐like characteristics, which simultaneously have dual enzyme‐like activities. Moreover, the covalent modification of Au NPs with graphene oxide cannot affect their GOx‐like activity. Furthermore, a one‐pot enzyme‐free strategy is developed for the fast colorimetric detection of glucose.